Nucleosome in patients with systemic sclerosis: possible association with immunological abnormalities via abnormal activation of T and B cells. Issue 10 (13th November 2015) - Yoshizaki, Ayumi; Taniguchi, Takashi; Saigusa, Ryosuke; Fukasawa, Takemichi; Ebata, Satoshi; Numajiri, Hiroko; Nakamura, Kouki; Yamashita, Takashi; Takahashi, Takehiro; Toyama, Tetsuo; Asano, Yoshihide; Tedder, Thomas F; et al.
Abstract : Objective: To determine the serum levels of nucleosome in patients with systemic sclerosis (SSc) and relate the results to the clinical features of SSc. Methods: Serum nucleosome levels in 91 patients with SSc were examined by ELISA. The expression of Toll-like receptor (TLR) 9 in T and B cells was quantified by flow cytometric intracellular protein analysis. The effects of nucleosomes on lymphocytes were also analysed. Moreover, we assessed the effects of nucleosomes on fibrosis, using wild type and CD19-deficient bleomycin-treated mice, an experimental model for human SSc. Results: Serum nucleosome levels were elevated in SSc compared with healthy controls and correlated positively with the extent of skin and pulmonary fibrosis and immunological abnormalities. The retrospective longitudinal analysis showed the serum nucleosome levels to be attenuated during the follow-up period. TLR9, which can be stimulated by nucleosome expression was upregulated in the affected T and B cells of patients with SSc. Moreover, nucleosome stimulation strongly increased interleukin (IL)-4 and IL-17 expression of T cells, B-cell IgG production and proliferation of lymphocytes in SSc compared with those in healthy controls. In bleomycin-induced SSc model mice, serum nucleosome levels were elevated compared with control mice. Furthermore, nucleosomes increased IgG production and proliferation of mouse B cells. Although TLR9 expression was similar between wild type and CD19-deficient splenic B cells, CD19 deficiency reduced these nucleosome effects. Conclusion: These results suggest that nucleosomes and its signalling in B and T cells contribute to disease development in SSc via TLR9.